HUMAN HEPATIC NATURAL KILLER CELLS IN HEALTH AND MALIGNANCY - HARMON, CATHAL (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
The adult human liver is described as an immunologically tolerogenic organ, maintaining a homeostatic environment while bombarded by dietary antigens, microbial products and metabolic by-products. The liver is also a site of immunosurveillance, scouring the portal vein and liver parenchyma for viral infection, malignant cells and toxic products. This balance is achieved through the unique immune repertoire of the liver. A predominance of immunoregulatory myeloid cells and cytotoxic innate lymphocytes, especially natural killer (NK) cells, creates a microenvironment skewed toward tolerance but primed to respond to pathogenic threats. We hypothesise that liver resident NK cells have adapted to this microenvironment, altering their phenotype and function in order to maintain an immunologically competent but naturally tolerogenic immune repertoire. We further hypothesised that tumour induced changes to the microenvironment compromise liver resident NK cell tumour immunity. In this project, we aimed to characterise NK cell subpopulations in healthy donor liver and metastatic liver tumours, focusing on the effect of the hepatic microenvironment on the differentiation and function of these populations. NK cells account for nearly 50% of hepatic lymphocytes, making it the most NK cell populated organ in the body. Unlike their peripheral blood counterparts, hepatic NK cells express an activated phenotype and display increased cytotoxicity toward tumour cells in vitro. However, this increased cytotoxic function is not accompanied by the usual production of classic pro-inflammatory cytokines, like IFN-γ. In this study, we have identified a population of tissue resident NK cells characterised by a unique transcription factor profile, Eomeshi Tbetlo, and expression of the tissue homing receptor CXCR6 whose ligand (CXCL16) is constitutively expressed by liver sinusoidal endothelial cells. When placed in culture, these cells revert to a more conventional phenotype but maintain CXCR6 expression. When this system is supplemented with conditioned medium from healthy liver tissue, hepatic NK cells maintain their Eomeshi Tbetlo phenotype, indicating that the liver microenvironment plays an important role in defining their phenotype. We have identified TGF-β as the factor responsible for maintaining this phenotype and suppressing pro-inflammatory cytokine production. Hepatic NK cells appear ideally suited for tumour surveillance. The tumour microenvironment is classically considered an anti-inflammatory environment; however tumour growth, angiogenesis and eventual metastasis requires an inflammatory environment, often provided by the immune cells trying to prevent the spread of cancer. Eomeshi Tbetlo hepatic NK cells have the potential to target tumour cells without contributing to the inflammatory environment which causes significant tissue damage and promotes tumour progression. In our cohort of colorectal liver metastasis (CRLM), NK cells are significantly depleted from these tumours, specifically the liver resident CD56bright NK cells. Culture with conditioned media from tumours selectively induces apoptosis of liver resident NK cells in vitro. Accumulation of lactate in the tissue microenvironment causes a decrease in intracellular pH, increased mitochondrial stress and production of ROS which induces apoptosis. This process can be abrogated by treatment with a mitochondrial ROS scavenger. We have identified a unique population of tissue resident anti-tumour NK cells in human liver. This population is compromised in CRLM through changes in the metabolic microenvironment. We propose that patients will benefit from metabolic targeted therapies which would restrict tumour growth, reduce lactate production and restore liver resident NK cell immunity. This is the first time tumour metabolism has been identified as a key immune evasion technique in CRLM and provides a novel avenue for therapeutic approaches.
APPROVED
Keywords: Natural Killer cells; malignancy; Metabolism